Vulnerability of the small island developing states of the Caribbean (UN ECLAC Port of SpainTT, 2000)
Approaches the vulnerabilities of small island developing states from three major perspectives viz. geo-economic; social; and, ecological/environmental.
Bibliography: p. 24